Experimental and numerical investigation of erosion in plugged tees for liquid-solid flow. (March 2023) - Zhao, Xiangyang; Cao, Xuewen; Zhang, Jianing; Cao, Hengguang; Zhang, Jun; Peng, Wenshan; Bian, Jiang
Highlights: The erosion profile was obtained through numerical and experimental studies. Particle trajectory analysis was carried out to understand the erosion generation. The erosion damage mechanism was discussed by the particle impact behavior. The location of maximum erosion is determined by the interaction of inertial and drag forces on the particles. Abstract: Sand particle erosion is a prevalent issue that cannot be ignored in oil field development and may lead to leakage accidents. Consequently, it is significant to investigate and quantify erosion in pipelines. In this study, a flow loop is utilized to study the erosion of plugged tees in liquid‒solid flow. Then, computational fluid dynamics (CFD) software ANSYS Fluent is used to develop an erosion prediction numerical model, and the numerical erosion profile is validated with the experiments. Through particle trajectory analysis, three representative particle movement paths are selected, which provides a deeper understanding of erosion generation. Additionally, the erosion damage mechanism is analyzed through the surface morphology of the samples and particle impact behavior. The findings reveal that particles can follow the secondary flow to impact the inside of the downstream pipe under the experimental flow conditions. As the particle size or liquid velocity increases, the particles begin to erode the outside of the pipe under the action of inertial force. Due to the low-angle impact of the particles, the corresponding erosion damage mechanism is micro-cutting.